The effect of a dietary supplement coriander seeds on the fatty acid composition of breast muscle in Japanese quail - Ertas, ON; Güler, T; Çiftçi, M; Dalkiliç, B; Yilmaz, O (Ecole Nationale Veterinaire Toulouse, 2005)
In human nutrition, a great challenge is to reduce saturated fatty acid consumption and to increase essential fatty acids (particularly n3 unsaturated acids) in alimentation. In this way, the aim of this study is to investigate the potential effects of dietary supplementation by coriander seed (considered as a lipolytic and antioxidant compound) on carcass lipid composition of quails. Five hundred ninety four, 3 day old Japanese quails were randomly divided into five groups (n = 99) according to dietary treatment. Four groups were fed with diet enriched by coriander seed with different dosages (0.5 - 1 - 2 and 4%) during 5 weeks and the fatty acid composition of the breast muscle lipids was analysed by gas chromatography. Values were compared to the control group (quails fed with basal diets). Dietary supplementation by coriander seed greatly affected the lipid composition of carcass by decreasing saturated fatty acid (SFA) contents (palmitic and stearic acids) and by increasing monounsaturated and polyunsaturated fatty acid (MUFA and PUFA) proportions in comparison to the control group (p < 0,0 1). The highest dosage of coriander seed (4% added to the ration) has systematically induced the greatest effects on fatty acid composition. Consequently, dietary supplementation by coriander seed would improve the quality of lipid carcass of quails by lowering SFA proportions and by enhancing contents of PUFA, particularly of n3 PUFA.
Keywords: Japanese quail; Coriander sativum; fatty acids; breast muscle; n3 poly-unsaturated fatty acid